Tinjauan Yuridis terhadap Pengadaan Tanah bagi Pelaksanaan Pembangunan Infrastruktur Jalan Tol Medan-Binjai - Zamharirah Zamharirah; Akmaluddin Syahputra (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Toll roads and other forms of infrastructure in Indonesia are highly dependent on land availability. Most of this is impacted by the way that the object of land obtaining is local area land that has been given over privileges, for the most part as confirmed and uncertified property freedoms. acquisition roads must also have their rights protected because land scarcity has always been a major obstacle to Indonesia's infrastructure development. Naturally, difficulties in acquiring land for infrastructure development may impede Indonesia's economic expansion. When land acquisition is carried out, the idea of legal rights to land and the significance of land to human life are taken into consideration. The 16.8-kilometer Medan-Binjai expressway framework advancement project is one of the Public Key Undertaking's activities. The normative juridical research method is used in this study, which looks at secondary data or library materials like laws and regulations, legal theories, and leading legal scholars' opinions. This exploration utilizes a subjective methodology, which is an examination that produces clear information investigation, in particular what the respondents state recorded as a hard copy or orally and furthermore genuine way of behaving, which is endlessly concentrated in general. While normative legal research with a qualitative approach is used in this study, field data results are also used. Keywoords: infrastructure, normative legal research, toll roads